Low temperature growth of diamond films on optical fibers using Linear Antenna CVD system. Issue 1 (January 2016) - Ficek, M.; Drijkoningen, S.; Karczewski, J.; Bogdanowicz, R.; Haenen, K.
Abstract: It is not trivial to achieve a good quality diamond-coated fibre interface due to a large difference in the properties and composition of the diamond films (or use coating even) and the optical fibre material, i.e. fused silica. One of the biggest problems is the high temperature during the deposition which influences the optical fibre or optical fibre sensor structure (e.g. long-period gratings (LPG)). The greatest advantage of a linear antenna microwave plasma enhanced chemical vapor deposition system (LA MW CVD) is the fact that it allows to grow the diamond layers at low temperature (below 300°C) [1]. High quality nanocrystalline diamond (NCD) thin films with thicknesses ranging from 70 nm to 150 nm, were deposited on silicon, glass and optical fibre substrates [2]. Substrates pretreatment by dip-coating and spin coating process with a dispersion consisting of detonation nanodiamond (DND) in dimethyl sulfoxide (DMSO) with polyvinyl alcohol (PVA) has been applied. During the deposition process the continuous mode of operation of the LA MW CVD system was used, which produces a continuous wave at a maximum power of 1.9 kW (in each antenna). Diamond films on optical fibres were obtained at temperatures below 350°C, providing a clear improvement of results compared to our earlier work [3]. The samples were characterized by scanning electron microscopy (SEM) imaging to investigate the morphology of the nanocrystalline diamond films. The film growth rate, film thickness, and optical properties in the VIS-NIR range, i.e. refractive index and extinction coefficient will be discussed based on measurements on reference quartz plates by using spectroscopic ellipsometry (SE).